Perceived crime severity and support for restorative justice in Singapore - Ngo, Jolene Xin Yi (Nanyang Technological University, 2021)
Restorative justice – which encourages offenders to take responsibility for their actions and make genuine reparations to their victims – is applied to crimes of varying severity in Singapore, but to a limited extent. Public opinion impacts the implementation of crime policies, however literature on perceptions of restorative justice is limited. The current study utilizes a within-subjects experimental design to investigate if, as perceived crime severity increases, there will be (a) less support for a purely restorative procedure and (b) more support for the mixed restorative justice procedure. The study sampled (N = 289) adults aged 18 years and above from the community. After reading a description of victim-offender mediation, participants read six different types of crime vignettes, then reported perceived severity, support for pure restorative and the mixed procedure for each vignette. Consistent with the first hypothesis, there was less support for the use of the pure restorative procedure for more severe crimes (p = .00). Contrary to the second hypothesis, there was less support for the use of the mixed restorative procedure for more severe crimes (p = .00). The results show some support for pure restorative procedures to be applied to nonviolent, low-severity offenses, and that crime severity alone cannot account for support for the mixed restorative justice procedure. This supports previous literature that just deserts motives are sensitive to mitigating factors that influence perceptions of offender punishment deservingness. The effects of fear of victimization and rehabilitative attitudes on support for restorative justice are possible avenues for future research.